Generazione Jakarta. (Im)mobilità e neoliberismo ordinario tra i giovani di Louga (Senegal) - Bruno Riccio; Guido Nicolas Zingari (Archivio Antropologico Mediterraneo)
In this article we discuss the representations ad aspirations of Louga’s Jakarta men in Senegal. This is the name of Asian made moto-taxi drivers, an activity through which many young persons managed to enter the informal economy of various Senegalese Towns. Their experiences show that, despite growing vulnerability, youth are not passive or immobile actors towards social duties, kin relations or the town’s economic activities. Through the rielaboration of ordinary ethics and forms of social and spatial mobilities, they seem protagonists of a reinterpretation from below of the neoliberal contradictory dicourses and policies characterizing the migration-development nexus. Yet, this ordinary neoliberism limits the understanding and politicisation of inequalities and contradictions of their precarious socio-economic condition. The Jakarta generation remains partially invisible and its horizon and potential purpose ambivalent although open to multiple explorations, which escape categorical classifications often found in development as much as migration studies.